2016
DOI: 10.5455/aim.2016.24.244-247
|View full text |Cite
|
Sign up to set email alerts
|

DWI/ADC in Differentiation of Benign from Malignant Focal Liver Lesion

Abstract: Material and methods:The study was of prospective-retrospective character. It was carried out at the AKH in Vienna (Austria), where 100 patients with focal liver lesions were included in the study. All

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
3
17
0
1
Order By: Relevance
“…Diffusion-weighted imaging is an MRI method that can also be used for detecting inflammatory/tumoral diseases in the abdomen [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging is an MRI method that can also be used for detecting inflammatory/tumoral diseases in the abdomen [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency in ADC cutoff points is probably attributable, among other reasons, to differences between scanners and differences in the parameters used to obtain diffusion-weighted images and ADC maps. [22,29,30] In our subgroup analysis restricted to benign lesions, adenomata and FNH exhibited ADC values of 1.41×10 − 3 mm 2 /s and 1.30×10 − 3 mm 2 /s respectively; both are intermediate values, and are not signi cantly difference between one another or in comparison with the ADC values found in malignant lesions. The application of DWI and ADC mapping in the characterization of certain benign solid liver lesions and the potential of this technique to distinguish benign lesions from malignant ones is still a topic of discussion.…”
Section: Adc and Adc Ratio Valuesmentioning
confidence: 57%
“…Sample size was calculated in the WinPepi software suite, based on previously reported results from the literature [14,[20][21][22][23]. These calculations showed that, to detect a signi cant difference between the ADCs of benign and malignant lesions, at the 5% signi cance level, with a statistical power of 80%, at least 65 lesions would have to be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of ADC values in diagnosis of malignancies of liver, breast, uterus, cervix have been widely studied. [7][8][9][10] Few similar studies have explored the limitations and diagnostic challenges faced while using DWI/ADC to detect pancreatic malignancies. [11,12] In our study, the ADC value in pancreatic malignancies (n=14) ranged from 0.850 x 10 -3 -1.14x10 -3 /s with a mean ADC value of 0.9340×10 −3 mm 2/ /s±0.07 which was found to be pointedly lower than the normal control group of 1.36326 × 10 −3 mm 2 s±0.16 (p<0.0005), (Figure 1c) thus clearly defining the utility of DWI/ ADC in such cases.…”
Section: Discussionmentioning
confidence: 99%